Maid from the Philippines isang manwal para sa domestic workers sa Hong Kong, Singapore at Malaysia - Sta. Maria, Amparita S. (Ateneo Human Rights Center, 1998)
A comprehensive handbook for Filipino domestic helpers in Hong Kong, Singapore and Malaysia. It is a guide on how they can protect their immigrant rights and how their needs as overseas workers can be responded.